The Role of Academic Buoyancy in Reducing Foreign Language Anxiety Among EFL Students: A Literature Review - Yurni, Yurni; Triana, Novita (Universitas Batanghari Jambi, 2025)
Foreign language anxiety (FLA) is a major barrier for students learning English as a foreign language (EFL). This anxiety often reduces their willingness to communicate and achieve academically. This article explores the role of academic buoyancy as a contributing factor to FLA. Academic buoyancy focuses on routine setbacks such as mistakes, exam stress, and difficulty participating in class. Drawing on literature in educational psychology and applied linguistics, this literature review highlights how students with FLA manage cognitive appraisals, regulate emotions, and maintain motivation, which collectively reduce anxiety and enhance language learning. A conceptual framework is proposed to illustrate the potential of academic buoyancy as a buffer against FLA in EFL classrooms. The article also discusses implications for teaching.